MORPHOLOGICAL VARIATION AMONG ROBUSTA COFFEE (Coffea canephora) ACCESSIONS IN TEMANGGUNG AS A BASIS FOR SELECTION - Aswin Hendry Atmoko; Bagus Aradea; Brahmadha Alif Fayza Ramadhani; Annisa Nanda Oktavia; Eviolita Indrawati (Berita Biologi, 2026)
Robusta coffee (Coffea canephora) is a strategic commodity that contributes significantly to farmers' livelihoods in Temanggung Regency, Central Java. This study aimed to evaluate the morphological variation among 56 robusta coffee accessions collected from 17 districts to support selection. A total of 30 morphological characters from leaves, stems, flowers, and fruits were recorded following IPGRI (1996) and Coffee Industry Corporation (2016) descriptors. Morphological data were analyzed using the UPGMA method to construct a dendrogram and calculate similarity coefficients. The results revealed high morphological variation, particularly in apical stem color (reddish yellow to dark green), internode distance (2–10 cm), and ripe fruit color (yellowish green to dark red). Agronomically, short to medium internodes (2–5 cm) and monopodial stem growth were identified as desirable traits due to their association with higher productivity, compact canopy structure, and ease of management. Accessions PRK_2 and PRK_3 showed identical morphology (similarity coefficient 1.00), while TBR_1 and GMW_1 exhibited low similarity (<0.50), indicating significant genetic differentiation. The clustering pattern was not fully aligned with geographic origin, suggesting variations in planting material or local selection. In conclusion, morphological variation based on 34 characters demonstrates substantial genetic diversity, with apical stem color, internode distance, fruit color, and stem growth type identified as key traits for production-oriented selection.